Adaptation, Reliability, and Validation of the Turkish Version of the Bad Sobernheim Stress Questionnaire-Deformity in Patients With Adolescent Idiopathic Scoliosis - Akçay, Burçin; Kuru Çolak, Tuǧba; APTİ, ADNAN (Wolters Kluwer Health, 2023)
Background:There is a limited number of disease-specific outcome measurement scales in Turkish, which can be used for individuals with adolescent idiopathic scoliosis (AIS). The aim of this study was to translate, adapt, and evaluate the validity and reliability of the Turkish version of the Bad Sobernheim Stress Questionnaire-Deformity (TRv.BSSQD) questionnaire in Turkish patients with AIS.Objective(s):After the translation and back-translation process, the TRv.BSSQD and Scoliosis Research Society-22 questionnaires were completed in face-to-face interviews with 49 patients with AIS. The TRv.BSSQD questionnaire was readministered to the same patients 2 weeks later to assess test-retest reliability.Results:The Cronbach alpha value calculated for internal reliability was 0.806. The intraclass correlation coefficient values of the items of the TRv.BSSQD ranged from 0.809 (P < 0.001) (question 8) to 0.955 (P < 0.001) (question 7). The test-retest correlation coefficient for the item-total score was 0.960 (P < 0.001). Validity analysis showed a significantly positive correlation between the TRv.BSSQD total score and pain, self-image, and mental subgroup and the total scores of the SRS-22r scale (P < 0.05).Conclusions:This patient-reported outcome instrument, the TRv.BSSQD, showed good internal consistency, good reliability with test-retest analysis, and construct validity, suggesting that it is an appropriate assessment instrument for Turkish patients with AIS.
Keywords: Adolescent Idiopathic Scoliosis; Questionnaire; Scoliosis; Turkish Version